Additivated millet silage quality with crumbled corn with straw and cob (Research, Society and Development, 2020)
The objective of this study was to evaluate the bromatological composition of forage millet silage under the inclusion of different levels of disintegrated straw and cob corn (MDPS). The millet silage ADR500 cultivar received different amounts of MDPS (0, 5, 10 and 15%). The design was completely randomized with 4 treatments and 4 repetitions, totaling 16 experimental units. The dry matter (DM) content determined in silage differed as a function of the inclusion levels of (MDPS), with a variation of 26.53% for the control treatment and 38.69% for the treatment with higher inclusion level (MDPS). For the organic matter values found there was significant difference only from the treatment with 15% inclusion of (MDPS). Regarding crude protein (CP), a linear increase was observed as the levels of (MDPS) increased, ranging from 9.46 to 14.92%. The levels of (NDF) and (ADF) determined in silages ranged from 58.50 to 66.25% and 31.25 to 38.50% respectively. For the ether extract determined in forage millet silages with inclusion of (MDPS) ranged from 3.13 to 3.95%. The mineral matter content (MM) showed a significant difference as a function of MDPS inclusion levels, ranging from 5.26 to 7.55%. Therefore, it is concluded that the use of MDPS as a millet silage additive is feasible.